HOW THE PRIEST IS NOTICED? PRIEST’S IMAGE ACCORDING TO SYMBOLISM OF LITURGICAL VESTMENTS - Mielnik Dawid (Studia Warmińskie, 2017)
The main purpose of this paper is finding the answer to the question of how the priest who celebrates the Holy Mass is noticed according to symbolism of liturgical vestments which he wears. The method used in these researches is analysis of liturgical vestments symbolism which is ascribed to a particular garment. Thanks to finding the meaning of liturgical vestments it is possible to point out the common symbolism. These researches rely on garments which are used during the Tridentine Mass because in this kind of liturgy there are more vestments so there is richer symbolism. On the basis of analysis it can be claimed that there are two main directions. The first one is moral direction, the second one is Christology direction.